(untitled) (New Delhi, 2002)
Ramayana is one of the great epics of India. This story of Sri Rama by the great sage Valmiki is referred to as the Adi Kavya. Other famous versions of Ramayana include Shri Ram Charit Manas in avadhii by Goswami Tulasidas and Kambar's Kambaraamayanam in Tamil. The Ramayana has been a perennial source of spiritual, cultural and artistic inspiration, not only to the people of India but also to the people all over the world. It has helped to mould the Hindu character and has inspired millions of people with the deepest of love and devotion.
Keywords: Children's stories,Chuyện của trẻ em